Factors influencing the engagement of foreign students in short-term mobility program in Malaysia - Koo, Lee Feng; Ong, Sharon Yong Yee; Wong, Tze Jin; Ting, Zhang (Universidad de Las Palmas de Gran Canaria * Facultad de Geografia e Historia, 2024)
Technological advances and globalization have transformed the educational landscape, making it more competitive and sustainable. Student mobility is a critical indicator for evaluating the quality of higher education, particularly in terms of campus diversity and internationalization. The effects of mobility have been extensively researched, but little attention has been paid to the factors that influence the short-term mobility of international students. This study aims to address this gap by examining the factors that influence short-term mobility in relation to the location and facilities of higher education institutions (HEI) and the content of the study programme. Data were collected from 30 respondents from a technical university abroad who engaged in this short-term mobility program in Malaysia. The findings reveal that all key factors, including location (mean=4.267), duration (mean=4.500), content (mean=4.667), food and beverages (mean=4.667), and accommodation (mean=4.600), are crucial, with high mean scores above 4 on a 5-point Likert scale. Correlation analysis shows strong relationships, particularly between food and accommodation and the overall engagement of students. ANOVA results indicate no significant differences among the factors , emphasizing the need for a holistic approach in program development. The findings offer useful insights not only for improving short-term mobility, but also for guiding other potential mobility projects through the challenges of sustainable education in future.